Hubungan Kebiasaan Sarapan Pagi, Tingkat Kecukupan Protein dan Vitamin C dengan Kejadian Anemia di SMKN 12 Surabaya - Eldara Zanuba; Sri Sumarmi (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
Anemia is one of the nutritional issues that teenagers face. Anemia is a result of the predominance of nutritional intake that is subpar, which might result in a danger if nutritional issues exist. inadequate nutrient intake, which affects the body's ability to absorb nutrients or absorb them properly and contributes to hemoglobin production. Breakfast habits are another element that causes anemia. The value of breakfast in helping youngsters satisfy their daily nutritional and energy demands. The goal of this research was to examine the relationships between anemia at SMKN 12 Surabaya and breakfast practices, protein intake, and vitamin C intake. 100 young women from SMKN 12 Surabaya were the sample for the study, which employed cross sectional analysis. The study's independent factors were breakfast practices, protein intake, and vitamin C intake. The dependent variable was young women's anemia. The Chi-Square test is used in a bivariate study to examine the relationship between breakfast consumption, protein intake, and vitamin C intake, and the prevalence of anemia. 39% of respondents reported having anemia. The majority of respondents reported eating breakfast often with adequate amounts of protein (56%) and inadequate levels of vitamin C (93%). The frequency of anemia and the amount of protein adequacy are significantly correlated (p=0.005). Breakfast consumption had no discernible impact on the prevalence of anemia (p=0.522). The incidence of anemia and the amount of vitamin C adequacy did not significantly correlate (p=0.557). The prevalence of anemia in female teenagers is correlated with the amount of adequate protein in the diet.